2017
DOI: 10.1038/sdata.2017.141
|View full text |Cite
|
Sign up to set email alerts
|

A global database on freshwater fish species occurrence in drainage basins

Abstract: A growing interest is devoted to global-scale approaches in ecology and evolution that examine patterns and determinants of species diversity and the threats resulting from global change. These analyses obviously require global datasets of species distribution. Freshwater systems house a disproportionately high fraction of the global fish diversity considering the small proportion of the earth’s surface that they occupy, and are one of the most threatened habitats on Earth. Here we provide complete species lis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
200
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 184 publications
(210 citation statements)
references
References 32 publications
0
200
0
10
Order By: Relevance
“…In conclusion, our findings suggest that the difference in morphological distributions between the fish faunas of the six biogeographic realms is driven not only by the evolutionary divergence between realm fish faunas (Heino et al, ; Hugueny, ; Tedesco et al, ), but also by the distinct environmental constraints acting in each realm. Moreover, such morphological differences among realms translates into a shared strong contribution of morphologically extreme species among realms.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In conclusion, our findings suggest that the difference in morphological distributions between the fish faunas of the six biogeographic realms is driven not only by the evolutionary divergence between realm fish faunas (Heino et al, ; Hugueny, ; Tedesco et al, ), but also by the distinct environmental constraints acting in each realm. Moreover, such morphological differences among realms translates into a shared strong contribution of morphologically extreme species among realms.…”
Section: Discussionmentioning
confidence: 57%
“…Fish occurrence data can be retrieved freely from https://doi.org/10.6084/m9.figshare.c.3739145, and metadata are available in Tedesco et al (). Information about the 9,150 species with combined trait values (PC1–PC5) used in this study is provided as a supplementary (Table S5), which also indicates the morphologically extreme and most morphologically extreme species and the IUCN Red List status for each species.…”
Section: Data Accessibilitymentioning
confidence: 99%
“…This first global quantitative analysis of the biogeography of freshwater fishes is based on a large‐scale database compiling occurrence data from thousands of sources and is thus inevitably subject to errors and incomplete data (Tedesco et al, ). To minimize errors, a careful screening and correction procedure has been implemented for this database (see Tedesco et al, ). Reassuringly, the results obtained from other clustering methods as well as our sensitivity analysis suggested that the regions we identified are robust.…”
Section: Discussionmentioning
confidence: 99%
“…Global distribution of freshwater fish species richness per drainage basin based on the global database on freshwater fish species occurrence in drainage basins (Tedesco et al, ). Grey‐shaded areas correspond to basins without records of native strictly freshwater species [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Methodsmentioning
confidence: 99%
“…These disturbances can interact and their effects can accumulate in downstream systems (Jackson, Loewen, Vinebrooke, & Chimimba, ; Nõges et al., ; Schindler, ). As a result, extinction rates of freshwater biota are estimated to be 112–855 times higher than rates for terrestrial species (Collen et al., ; Tedesco et al., ). For example, between 1896 and 2006, 57 North American freshwater fish species went extinct (Burkhead, ) and, in Canada, 71 of the 207 native fish species are considered at risk by the Committee on the Status of Endangered Wildlife in Canada (Dextrase & Mandrak, ; Lamothe et al., In press).…”
Section: Introductionmentioning
confidence: 99%